Anaerobic power characteristics of elite athletes in national level team-sport games - Kalinski, M. I.; Norkowski, H.; Kerner, M. S.; Tkaczuk, W. G. (European Journal of Sport Science, 2002)
Purpose: The purpose of the study was to acquire current anthropometric and physiological profiling of elite athletes and to examine differences in the characteristics. Methods: Three hundred and sixteen male, team-sport athletes were evaluated for anaerobic performance using the Wingate anaerobic test. Results: MANOVA procedures indicated significant differences in height among players of the sports. Pearson correlations indicated strong correlations for body mass with absolute peak power (Pp) and mean power (Pm), and relative Pm. Height correlated strongly with absolute Pp and Pm, with a low correlation with relative Pp. MANOVA procedures indicated that athletes who specialized in handball, volleyball, and basketball attained the greatest relative and absolute Pp, and the greatest relative Pm. Relative and absolute Pp of the soccer athletes were lowest of all other elite athletes. Conclusion: This study introduces normative values for elite male athletes, empowering coaches in the evaluation of anaerobic abilities and in the objective selection of athletes for competition.